2018
DOI: 10.1159/000490421
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Clot Retrieval by Hub-and-Spoke Service Delivery is Feasible Compared with Direct-to-Mothership

Abstract: Background: Endovascular clot retrieval (ECR) improves outcomes for acute ischaemic stroke with large artery occlusion. However, the provision of ECR requires resource-intensive comprehensive stroke centres (CSC), which are impractical to establish in regional hospitals. An alternative is a “hub-and-spoke” model, whereby ischaemic strokes are triaged at the regional primary centres and where eligible, transferred to a CSC. We aimed to compare the outcomes of patients directly admitted to a CSC with patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
0
10
1
Order By: Relevance
“…34 During the COVID-19 pandemic, there will be new challenges in triaging stroke patients with suspected or confirmed COVID-19 infection, who cannot be transferred rapidly to angiographic suite from ED or from outside the hospital due to added requirements. Inter-facility transfer, which occurs in 44%-72% of acute ischemic stroke patients 41,42 may require special equipment and personnel that are likely to delay the procedure. Due to expected challenges, intravenous rt-PA in an isolation ward, rather than percutaneous coronary intervention has been recommended for patients with acute myocardial infarction.…”
Section: Section 9 Mechanical Thrombectomymentioning
confidence: 99%
“…34 During the COVID-19 pandemic, there will be new challenges in triaging stroke patients with suspected or confirmed COVID-19 infection, who cannot be transferred rapidly to angiographic suite from ED or from outside the hospital due to added requirements. Inter-facility transfer, which occurs in 44%-72% of acute ischemic stroke patients 41,42 may require special equipment and personnel that are likely to delay the procedure. Due to expected challenges, intravenous rt-PA in an isolation ward, rather than percutaneous coronary intervention has been recommended for patients with acute myocardial infarction.…”
Section: Section 9 Mechanical Thrombectomymentioning
confidence: 99%
“…Systematic search retrieved 18 studies including 7,017 patients (PRISMA flowchart) ( Figure 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most of the included studies were observational and prospective, only one study was a RCT 15 (Table 1). As a result, quality of studies ranged fair to good, with only one RCT achieving optimal score on risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic search retrieved 18 studies including 7,017 patients (PRISMA flowchart) ( Figure 1 ) [ 10 - 27 ]. Most of the included studies were observational and prospective, only one study was a RCT [ 15 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was based on a retrospective analysis of prospectively collected data from a single centre, which limits applicability to regions with different geography and population density. We did not analyse patient outcomes according to treatment during business hours versus after hours, which has been shown to influence workflow time metrics 9. Although there was no difference in baseline characteristics between transferred and direct presenter groups, we cannot exclude a (favourable or unfavourable) selection bias in transferred patients.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study based in Victoria found no difference in 90-day functional outcomes between transferred and direct to CSC presenters undergoing EVT9; however, international registries have demonstrated poorer outcomes in transferred patients 10–12. New South Wales and other Australian states have different geographical challenges from Victoria.…”
Section: Introductionmentioning
confidence: 98%